Effect of Social Media Marketing of Luxury Brands on Brand Equity, Customer Equity and Customer Purchase Intention - Rizwan Raheem Ahmed; Erum Zahoor Zaidi; Syed Hasnain Alam; Dalia Streimikiene; Vishnu Parmar (Amfiteatru Economic, 2023)
The study conducted primarily examined the effect of Social Media Marketing Effect on Brand equity in creating Purchase Intention and Customer equity. For this purpose, we employed structural equation modeling using Smart-PLS 3.0, the data of 312 respondents were collected through structured questionnaire. The findings show a significant positive relationship between Social Media Marketing and Brand Equity. The role of social media marketing efforts through Brand equity directly affects customer equity: The role of social media marketing efforts through Brand equity has a direct significant effect on Purchase Intention. Brand equity relates positively to customer equity. Brand equity relates positively and significantly to purchase intention. Brand equity has a significant and positive mediating effect on the relationship between marketing efforts on social media (SMMEs) and consumer equity. The study unfolds an exciting dimension that social media marketing, a hype in the haute couture and Preto Porte have a significant impact on purchase intention and Customer Equity in the Pakistani market. A more comprehensive marketing strategy has to be adopted in the Pakistani market. The Pakistani customer is more influenced to purchase haute couture by testing and trial sessions besides purchasing online. There are few online Brand communities in the Pakistani market where customers can interact with other users who share common interests and can talk about luxury brands. Theoretically, this study ascertains the customer lifetime value of luxury brands. The intense competition in luxury fashion brands also leads to strong customer equity created by Social Media Marketing.
Keywords: C12; L6; L67; M3; 330; social media marketing efforts; brand equity; purchase intention; customer equity; brand satisfaction; haute couture; structural equation modeling.